Linking Agriculture and Tourism Through the Strategic Alliance Model: A Pathway to Sustainable Local Economies - Susanti, Jeni; Wahyuni, Luh Mei; Astawa, I Putu Mertha (Indonesian Scientific Publication, 2025)
This research explores the integration of Bali’s agricultural and tourism sectors through a strategic alliance framework as a pathway to sustainable local economic development. It responds to the challenge that the potential synergy between these sectors has not been fully utilized and is increasingly at risk due to land conversion, environmental pressures, and cultural transformation resulting from rapid tourism expansion. The novelty of the study lies in combining three complementary theoretical perspectives, strengthening supply chain relationships, integrating the tourism value chain, and promoting pro-poor tourism—into a single contextually grounded model. Employing a qualitative case study approach, data were collected from 12 key informants and 50 tourists using interviews, focus group discussions, and field observations. The analysis indicates strong market opportunities supported by economic, social, and technological drivers, yet practices across the five alliance components remain disjointed and lack coordination. The proposed model offers a practical contribution by linking theory to application, creating a framework that can improve farmers’ livelihoods, safeguard cultural traditions, and reinforce Bali’s competitiveness as a sustainable tourism destination.